PAEDIATRICS BRAIN IMAGING IN EPILEPSY: COMMON PRESENTING SYMPTOMS AND SPECTRUM OF ABNORMALITIES DETECTED ON MRI - Ali, Azmat; Akram, Faiza; Khan, Ghayyur; Hussain, Shaukat (Journal of Ayub Medical College Abbottabad, 2017)
Background: Epilepsy, a common neurological disorder can present at any age and has a number of aetiologies with underlying brain disease being the most common aetiology. Brain imaging becomes important and mandatory in the work up for epilepsy in localization and lateralization of the seizure focus. Methods: This cross-sectional study was conducted in the department of Radiology Ayub Medical Teaching Institution Abbottabad from 1st March 2015 to 31st March 2016. A total of 209 children aged 28 days to 14 years were included in the study who presented with seizures to clinicians. Information obtained from history, clinical examination and investigations especially MRI brains were recorded in a prescribed pro forma. The data was analysed in SPSS 20. Results: MRI examination was unremarkable in 44.01% (n=92) and mild generalized brain atrophy was noted in 12.91% (n=27). Arachnoid cysts, mild unilateral brain atrophy and hydrocephalous due to aqueduct stenosis were recorded in 3.82% (n=8) of each group. Neoplastic lesions were the second most common abnormal MRI finding and constituted 5.74% (n=12). Leukodystrophy was diagnosed in 4.78% (n=10). MRI examination showed ring enhancing lesions (tuberculomas) and AVM in 1.43% (n=3) of each group. Perinatal ischemia and intracranial infection, (focal or generalized) were recorded in 2.87% (n=6) of each group. A 0.95 % (n=2) of children in each group had agenesis of corpus callosum and cavernoma. The radiological MRI diagnosis of Raussmussen encephalitis was made in 3.34% (n=7). Single case, each of mesial temporal sclerosis, subdural haemorrhage, infarct and craniopharyngioma was recorded making 0.47 % of the total patients in each case. Conclusion: MRI examination was abnormal in significant number of patients (55.86%), so therefore if properly utilized, in a good clinical context, this can identify most of the structural brain abnormalities in paediatric patients presenting with seizures. Keywords: Brain imaging; MRI; epilepsy; Paedriatics; Abnormalities; Radiology